Laboratory analysis and ray visualization of diffractive optics with enhanced intermediate vision - Son, Hyeck Soo; Łabuz, Grzegorz; Khoramnia, Ramin; Yildirim, Timur Mert; Auffarth, Gerd U. (BMC ophthalmology, 2021)
To assess the optical behavior of a new diffractive intraocular lens (IOL) and compare its performance to that of an established extended-depth-of-focus (EDOF) IOL.